2020
DOI: 10.1088/1361-6595/abab55
|View full text |Cite
|
Sign up to set email alerts
|

The formation of atomic oxygen and hydrogen in atmospheric pressure plasmas containing humidity: picosecond two-photon absorption laser induced fluorescence and numerical simulations

Abstract: Atmospheric pressure plasmas are effective sources for reactive species, making them applicable for industrial and biomedical applications. We quantify ground-state densities of key species, atomic oxygen (O) and hydrogen (H), produced from admixtures of water vapour (up to 0.5%) to the helium feed gas in a radio-frequency-driven plasma at atmospheric pressure. Absolute density measurements, using two-photon absorption laser induced fluorescence, require accurate effective excited state lifetimes. For atmosphe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(92 citation statements)
references
References 78 publications
5
87
0
Order By: Relevance
“…Recently, Schröter et al [27] reported H atom density measurements in the effluent of a CAPJ, operating with humidified He, which have been obtained with a picosecond TALIF laser and imaging system. The picosecond time resolution allows an independent and direct measurement of the effective (reduced) lifetime of the excited state.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Schröter et al [27] reported H atom density measurements in the effluent of a CAPJ, operating with humidified He, which have been obtained with a picosecond TALIF laser and imaging system. The picosecond time resolution allows an independent and direct measurement of the effective (reduced) lifetime of the excited state.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a plethora of experimental and numerical studies has emerged. These studies validated the excellent capability of TALIF to determine atomic densities in flames and plasmas [28,36,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. The concept of this method is depicted in Figure 2.…”
Section: Talif Principles Involved Theory and Experimental Requirementsmentioning
confidence: 56%
“…This is reasonable since the main goal of those works is the determination/manipulation of the absolute densities of reactive atomic species, and the understanding of their dynamics in the plasmas studied. This has also been the case for some recent ps-and fs-TALIF investigations focusing on the measurement of O-and H-atom densities in non-equilibrium plasmas [44,45,90,91].…”
Section: Challenges When Using Ns-and Ps/fs-talif In Plasmasmentioning
confidence: 71%
See 1 more Smart Citation
“…Such diagnostics aim for the precise identification and fine tuning of essential physical quantities, leading to a better understanding of transient phenomena in reactive plasmas. Typical examples refer to the use of (i) two-photon absorption laser induced fluorescence (TALIF) to obtain atomic densities [1,5,[7][8][9][10][11][12][13][14], (ii) electric-field-induced second harmonic generation to infer electric field dynamics [1,6,10], and (iii) Thomson scattering to access electron density and temperature [15,16]. These measurements can help in the development of diverse plasma-based applications, e.g.…”
Section: Introductionmentioning
confidence: 99%